2021
DOI: 10.1021/acsami.1c04451
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Exfoliated Graphene for High-Durability Cement Composites

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…In contrast to the coating method, direct doping of graphene materials can demonstrate the impermeability and overall strength of cemented materials and prevent the erasure of chloride ions and the rusting of internal steel rods. Regarding microstructure and permeability resistance theory, Krystek et al [ 67 ] attributed the chloride ion resistance to the shrinkage of large capillary pores. Similarly, Zhou et al [ 68 ] found through simulation that the incorporation of graphene materials led to the remodeling of microstructure and inhibited the migration of water in the pores of cement slurry.…”
Section: Durabilitymentioning
confidence: 99%
“…In contrast to the coating method, direct doping of graphene materials can demonstrate the impermeability and overall strength of cemented materials and prevent the erasure of chloride ions and the rusting of internal steel rods. Regarding microstructure and permeability resistance theory, Krystek et al [ 67 ] attributed the chloride ion resistance to the shrinkage of large capillary pores. Similarly, Zhou et al [ 68 ] found through simulation that the incorporation of graphene materials led to the remodeling of microstructure and inhibited the migration of water in the pores of cement slurry.…”
Section: Durabilitymentioning
confidence: 99%
“…When the sulfate ions are transferred to the tunnel lining concrete, these react with the Ca 2+ generated by the dissolution of CH and C–S–H to form gypsum (CS̅H 2 ) (see eq ). The gypsum (CS̅H 2 ) further reacts with unhydrated aluminates to form ettringite (C 6 AS̅ 3 H 32 ), as shown in eqs –: , …”
Section: Chemo-damage-transport Modelmentioning
confidence: 99%
“…The application of nanoparticles (NPs) in concrete and its potential benefits for improved strength and durability performance are well acknowledged. This stems from the fact that the application of supplementary cementitious materials (SCM) finer than cement and the resulting improvements in strength and durability increase with increasing fineness of SCM, which is attributed to packing density enhancement and reduction of calcium hydroxide (CH) content. The adoption of microsilica and subsequently nanosilica (SiNPs) has been attempted to exploit the benefits of improved packing density and pozzolanic reactivity of the material. In addition to SiNPs, a wide range of NPs including Al 2 O 3 , TiO 2 , Fe 2 O 3 , CaCO 3 , CuO, etc., have been explored to improve the mechanical, thermal, and electrical properties of cement systems. Of the above, SiNPs on account of their superior pozzolanic and microstructure properties have received wider attention from the researchers.…”
Section: Introductionmentioning
confidence: 99%